Experimental investigation of passively cooled photovoltaic modules on the power output performance - Emy Zairah Ahmad; Kamaruzzaman Sopian; Adnan Ibrahim; Chin Kim Gan; Mohd Suffian Ab Razak (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The power output performance of a photovoltaic (PV) module decreases as the temperature increases. The increase in module temperature above the standard test conditions (25 ⁰C) could reduce the average power output by at least 0.2% for each 1 ⁰C rise. Hence, keeping the module temperature low is necessary for PV systems exposed to high solar irradiance throughout the year. Therefore, this study aims to experimentally analyse the eletctrical performance of passively cooled PV modules in the tropics. The developed cooling approach consists of rectangular plate fins made of aluminum 6061, attached to the rear surface of tedlar layer. The results indicated that the average module temperature reduction of 3.25 ⁰C was observed under outdoor exposures. As a result, the heat sink improved the overall power output up to 14.2%. As the PV performances are site-dependent, these findings are beneficial as it provides a thorough explanation of fin heat sink behavior under long-term field exposures of tropics.